Konflik Batin Tokoh Utama dalam Cerpen Sumidagawa Karya Nagai Kafu (Kajian Psikologi Sastra Kurt Lewin) - Muhammad Miqdad; Antonius R. Pujo Purnomo (Ayumi : Jurnal Budaya, Bahasa, dan Sastra, 2023)
The focus of this research problem discusses the inner conflict experienced by Chokichi as the main character in the short story Sumidagawa by Nagai Kafu which has a background in the Meiji era. This study uses the conflict theory put forward by Lewin, which divides inner conflict into three, namely approach-approach, approach-avoidance and avoidance-avoidance conflict. The purpose of this study is to identify and interpret the form of inner conflict in the main character in the short story Sumidagawa by Nagai Kafu. The benefit of this research is to contribute to the development of science, especially in Japanese literature in Indonesia. For general readers, it is hoped that this research article can introduce Nagai Kafu’s work as a reading reference, especially for the Sumidagawa short story, as well as a means for readers to appreciate contemporary works of Japanese literature. This research method use a descriptive qualitative analysis method to analyze each form of the main character’s inner conflict in each storyline of Sumidagawa short story. The data source for this research comes from the Sumidagawa short story by Nagai Kafu which is contained in the Aozora Bunko digital library along with an Indonesian translation book entitled Sungai Sumida which is included in the Collection of Japanese Short Stories by Hanafi (2017). The results of research on Chokichi’s inner conflict based on Lewin’s conflict theory show that he experiences a form of approach-avoidance conflict and avoidance-avoidance conflict. This form of inner conflict is represented in Chokichi in the form of desires that are not in line with reality, disputes that are not in line with the will, and confusion in dealing with a problem. Keywords: Chokichi; inner conflict; Meiji; Nagai Kafu; Sumidagawa.